Albania : Joint Staff Assessment of the Poverty Reduction Strategy Paper Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This report presents the Joint Staff Assessment of the Poverty Reduction Strategy Paper Annual Progress Report (APR) for Albania. The second year of National Strategy for Socio-Economic Development (NSSED) implementation in Albania saw significant improvements in a number of areas, despite continuing political uncertainties and governance issues. The APR presents an appropriate analysis of poverty, recent economic developments, and sectoral reforms. The IMF staff commends the government for using information from the Living Standard Measurement Survey and other sources to analyze patterns in living standards and to enrich its previous diagnoses of poverty.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet